2006
DOI: 10.1002/neu.20256
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar and typical oligodendrocytes are involved in an uneven myelination pattern during the ontogeny of the lizard visual pathway

Abstract: We studied the myelination of the visual pathway during the ontogeny of the lizard Gallotia galloti using immunohistochemical methods to stain the myelin basic protein (MBP) and proteolipid protein (PLP/DM20), and electron microscopy. The staining pattern for the PLP/DM20 and MBP overlapped during the lizard ontogeny and was first observed at E39 in cell bodies and fibers located in the temporal optic nerve, optic chiasm, middle optic tract, and in the stratum album centrale of the optic tectum (OT). The expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 33 publications
3
16
0
1
Order By: Relevance
“…microtubules, nestin) might be sufficient to preserve the cell morphology under normal physiological conditions, although not after retinal insults (Lundkvist et al 2004). The proximity of loose myelin and Müller processes in the PR and the apparent absence of glial cells in this region indicate they cooperate in myelination as suggested previously (Santos et al 2006) Interestingly, in G. galloti, Müller glia express Pax2 only in the CR, as reported in zebrafish and chick (Boije et al 2010;Stanke et al 2010). However, retinal astrocytes are the only astroglia expressing Pax2 in mammals.…”
Section: Discussionsupporting
confidence: 73%
“…microtubules, nestin) might be sufficient to preserve the cell morphology under normal physiological conditions, although not after retinal insults (Lundkvist et al 2004). The proximity of loose myelin and Müller processes in the PR and the apparent absence of glial cells in this region indicate they cooperate in myelination as suggested previously (Santos et al 2006) Interestingly, in G. galloti, Müller glia express Pax2 only in the CR, as reported in zebrafish and chick (Boije et al 2010;Stanke et al 2010). However, retinal astrocytes are the only astroglia expressing Pax2 in mammals.…”
Section: Discussionsupporting
confidence: 73%
“…Because newly hatched lizards require a functional visual system to survive in their natural environment, abundant BDNF staining at this stage may be a key factor mediating experience-dependent effects on RGCs (Landi et al, 2007). In this respect, the temporo-spatial staining pattern of fibers is reminiscent of that of the myelination process (Santos et al, 2006) although BDNF staining in putative myelinating cells was undetected during development. As BDNF is essential for myelination and remyelination by Schwann cells (Zhang et al, 2000;Chan et al, 2001) and BDNF KO mice have hypomyelinated RGCs axons (Cellerino et al, 1997), we hypothesize that RGCs expressing BDNF might also regulate myelination of lizard RGC axons by local influence on oligodendrocytes.…”
Section: Bdnf Distribution Pattern Across Phylogenymentioning
confidence: 92%
“…25 Previous studies have shown that axons are myelinated in some lower vertebrate retinas, such as in chickens, lizards, and goldfish. [2][3][4][5] Despite a lack of transgenic lines, they simply described myelination and the different developmental states of OLs by immunohistochemistry and TEM evidence. Using olig2 zebrafish, 12 we can quantitatively observe the temporal dynamics of myelination in zebrafish retinas.…”
Section: Discussion Myelination In Zebrafish Retinasmentioning
confidence: 99%
“…5). 22 Although retinal myelination has been reported in some lower vertebrates, such as chickens, lizards, turtles, and fish, [2][3][4][5] no study has related the functional characterization of myelin in retinas. Lysophosphatidylcholine can induce rapid and highly reproducible demyelination in the CNS without producing much damage to the axons.…”
Section: The Function Of Ols In Zebrafish Retinasmentioning
confidence: 99%
See 1 more Smart Citation